Fundamentals of power system economics - Kirschen, Daniel Sadi (John Wiley & Sons, 2004)
The introduction of competition into the electricity supply industry has fundamentally changed the way it works. In light of these changes this book provides a clear and comprehensive explanation of the basic principles underpinning the design and operation of modern competitive electricity markets.